NOTARY RESPONSIBILITY FOR ELECTRONIC STORAGE OF NOTARY PROTOCOLS - Ngadino Ngadino (UNISSULA, 2021)
The notary protocol is a state archive that must be kept and guarded by a notary public. Due to security concerns, maintenance costs and the size of space required further electronic storage of notary protocols can be carried out. This legal research uses a normative juridical approach as a result of the absence of norms. The technique of using legal materials used is the card system technique. The results show that the notary protocol that is stored electronically is important to do considering the duties of a notary as a public official who has the task of searching for the public in the field of civil cases so that the state must make rules regarding the storage of notary electronic protocols in its arrangement with Cyber Notary. The mechanism is to use the transfer media in digital form or scanning. The strength of notary protocol evidence stored in the field of civil law only functions as a backup, not as an electronic one which has binding power because it does not meet the requirements for document authenticity as regulated in Article 1 paragraph. 7 of the Amendments to the Law on Notaries and Article 1868 of the Civil Code and in the field of criminal procedural law, namely that it can be evidence to show evidence that shows other evidence.